MANAGEMENT OF PRODUCTION RESOURCES OF AGRICULTURAL ENTERPRISES IN UKRAINE: A CASE STUDY OF VOLYN REGION - Mykola DZIAMULYCH; Svitlana ROGACH; Olha SHULHA; Nazar STUPEN; Alla TENDYUK; Liudmyla STRYZHEUS; Andrii BILOCHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article aimed to analyze resources management of an agricultural enterprise in Ukraine. It proved that the resource potential of agricultural enterprises is a necessary element of the management system. The need for strategic management of resource potential is determined by the fact that in modern conditions, inefficient use of resources reduces the competitiveness of enterprises and makes their activities irrational. According to the results of the study, we substantiated that the development of a methodology for the formation of a resource strategy offers an opportunity for the enterprise to ensure the effectiveness of the process of providing its own resources. The given factors and conditions of strategic management of the resource potential of agricultural enterprises contribute to the further development of applied aspects of the use of the theory of resource potential by enterprises in the field of agriculture.